Electro-activation of O2 on MnO2/graphite felt for efficient oxidation of water contaminants under room condition. (November 2019) - Sun, Min; Fang, Li-Ming; Liu, Jia-Qin; Zhang, Feng; Zhai, Lin-Feng
Abstract: The activation of oxygen (O2 ) under room condition is highly desirable for oxidative removal of organic pollutants in water. Herein, we report a graphite felt (GF)-supported α-MnO2 catalyst which is active for activating O2 with assistance of an anodic electric field. The electro-assisted catalytic wet air oxidation (ECWAO) process on MnO2 /GF is able to rapidly degrade a variety of dyes, pharmaceutics and personal care products (PPCPs) under room condition. The congo red, basic fuchsin, neutral red and methylene blue are completely mineralized in 160 min, and the bisphenol A, triclosan and ciprofloxacin are mineralized by 89.9%, 81.5% and 65.4%, respectively, in 300 min. Mechanistic study indicates a surface-catalyzed non-free radical pathway for the oxidation of organic pollutants by O2 in the ECWAO process. The oxygen vacancies on MnO2 are identified as the catalytically active sites, at which oxygen atom is transferred from O2 to organic molecule through chemisorbed oxygen species. The anodic electric field assists such an oxygen transfer pathway by activating the complex of chemisorbed oxygen species and organic molecule through electro-oxidation reaction. The ECWAO process on MnO2 /GF electrode exhibits a great potential for practical wastewater treatment under room condition. Highlights: α-MnO2 on graphite felt is active to catalyze air oxidation in electric field. Electro-assisted catalytic wet air oxidation is developed under room condition. Oxygen vacancy on MnO2 is the active site for electro-activation of O2 . Chemisorbed oxygen species combine with organic molecule and electro-oxidized.